Afibrinogenemia - Nazrin, Tahera; Attawar, Pinkoo; Moniruzzaman, Md; Islam, I (Pulse, 2011)
Afibrinogenemia is a rare bleeding disorder with an estimated prevalence of 1:10,00,000 [1, 2]. It is an autosomal recessive disease resulting from mutations in any of the 3 genes that encodes the 3 polypeptide chains of fibrinogen and are located on the long arm of chromosome 4 3. Spontaneous bleeding, bleeding after minor trauma, and excessive bleeding during interventional procedures are the principal manifestations [2, 4]. Here we have reviewed the process of diagnosing a case of such rare disorder in Apollo Hospitals Dhaka. We have also highlighted the treatment and management plan of such a case. DOI: http://dx.doi.org/10.3329/pulse.v4i1.6964 Pulse Vol.4 January 2010 p.34-35